Prepregnancy Body Mass Index and Gestational Weight Gain Have No Negative Impact on Maternal or Neonatal Iron Status. (May 2016) - Cao, Chang; Pressman, Eva K.; Cooper, Elizabeth M.; Guillet, Ronnie; Westerman, Mark; O'Brien, Kimberly O.
Objective: To assess the impact of maternal obesity and excessive gestational weight gain (GWG) on maternal and neonatal iron status and to explore the possible mediating role of inflammation on hepcidin. Methods: This analysis included 230 pregnant adolescents (13-18 years) enrolled in either a longitudinal or a cross-sectional study. Prepregnancy body mass index (ppBMI) and GWG were obtained from medical records. Maternal iron status (hemoglobin, serum iron, ferritin, transferrin receptor, total body iron, and hepcidin) and inflammation (interleukin-6 [IL-6] and leptin) were assessed at midgestation (26.2 ± 3.3 weeks) in the longitudinal cohort and at delivery (39.8 ± 1.3 weeks) in both study cohorts. Cord blood was collected in both studies and analyzed for iron indicators. Results: Approximately 40% of the adolescents entered pregnancy overweight or obese. Multivariate analysis identified ppBMI as a negative predictor of serum iron at midgestation ( P = .009) and a positive predictor of serum hepcidin at delivery ( P = .02). None of the other maternal iron status indicators were significantly associated with ppBMI or GWG. Serum IL-6 was significantly positively associated with hepcidin at delivery ( P = .0001) but not at midgestation. There was a positive relationship between ppBMI and cord hemoglobin ( P = .03). Conclusion: These results suggest that adiposity-related inflammation does not override the iron-mediated signals that regulate hepcidin production during pregnancy, and in this adolescent cohort, there is no strong evidence for a detrimental effect of maternal obesity and excessive weight gain on iron status in the offspring at birth.